The regional distribution features of traffic safety or transport operation rules violations by persons who drive vehicles (Article 286 of the Criminal Code of Ukraine) - Novikov, Oleg (ScienceRise: Juridical Science, 2022)
The article is devoted to the regional peculiarities of the distribution of violations of traffic safety rules or operation of transport by persons driving vehicles (Article 286 of the Criminal Code of Ukraine). It is established, that the most criminally affected by violations of traffic safety rules or operation of transport by persons driving vehicles, in absolute terms, include: (1) Dnipropetrovsk region, (2) Odesa region, (3) Kyiv region, (4) Kharkiv region, (5) Lviv region, (6) Kyiv, (7) Donetsk region, (8) Zaporizhia region, (9) Zhytomyr region, (10) Rivne region. The most criminally affected regions of Ukraine in terms of population include such regions as: Rivne region (crime intensity rate per 100 thousand population - 55.10), Kyiv region (50.28), Volyn region (47.64), Chernihiv region (44.83), Mykolaiv region (43.54), Poltava region (39.36), Vinnytsia region (38.90), Odesa region (38.52), Zhytomyr region (36.47) and Kherson region (36.47). The safest regions were: Luhansk region (9.90), Donetsk region (16.15), Kyiv region (23.33), Khmelnytsky region (28.39), Sumy region (28.53). Regions-leaders in the number of violations of traffic safety rules or operation of transport by persons driving vehicles (Article 286 of the Criminal Code of Ukraine)per 100,000 vehicles were Volyn region (271.43), Vinnytsia region (199.22), Rivne region (148.92), Chernihiv region (127.20), Transcarpathian region (126.15), Mykolaiv region (124.08), Zhytomyr region (110.98), Kyiv region (107.40), Chernivtsi region (106.22), Kherson region (105,56). The regions with the lowest number of these criminal offenses per 100,000 vehicles were: Luhansk region (38.05), Cherkasy region (57.96), Donetsk region (70.36), Dnipropetrovsk region (73.76) and Kyiv (49.79). It is hypothesized, that the regional peculiarities of the distribution of violations of traffic safety rules or operation of transport by persons driving vehicles are comprehensively influenced by the population of the region, the number of available vehicles, freight and passenger traffic, road length, the region's expenditures on road improvement, crossing the region with international and national highways of national importance